Understanding and mitigating metallic anode degradation in divalent battery systems - Pu, SD (2022)
The work in this thesis focuses on the metallic anode in two of the divalent battery systems: aqueous zinc batteries and calcium-ion batteries. By performing systematic studies, we aim to provide a deep understanding of their anode degradation mechanisms: